2019
DOI: 10.1177/0883073819879276
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Brivaracetam in Pediatric Refractory Epilepsy: A Single-Center Clinical Experience

Abstract: Brivaracetam is a new antiepileptic drug with limited data in children. The objective of this study was to assess the efficacy/tolerability of brivaracetam. This is a retrospective chart review of children/adolescents with refractory epilepsy treated with brivaracetam from 2016 to 2018. The primary outcome was seizure reduction (decrease in seizure frequency >50%). Twenty-three patients were identified. Mean age at initiation was 12.5 years. Fourteen were females. Epilepsy was focal in 11, generalized in 6,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…In the McGuire et al retrospective study, 28 BRV was effective in 7 of the 11 patients with a history of focal seizures, representing the majority of the responders in the cohort (8 responders in a cohort of 20 patients). Three patients had mixed epilepsy, and one of those responded to BRV.…”
Section: Comparative Efficacymentioning
confidence: 96%
See 2 more Smart Citations
“…In the McGuire et al retrospective study, 28 BRV was effective in 7 of the 11 patients with a history of focal seizures, representing the majority of the responders in the cohort (8 responders in a cohort of 20 patients). Three patients had mixed epilepsy, and one of those responded to BRV.…”
Section: Comparative Efficacymentioning
confidence: 96%
“…The first data on the potential effect of BRV for the treatment of generalized seizures in pediatric patients were extrapolated from Strzelczyk et al 32 These authors reported a failure response to BRV in 70% of the 10 children studied, although the remaining 30% were seizure‐free for longer than 6 months. McGuire et al 28 also showed that BRV efficacy for generalized seizures was poor, with none of the treated patients reaching at least 50% of seizure reduction. However, the number of concurrent ASMs used in the non‐responder cohort was considerably higher compared to that of the responders (1.74 in a range of 1 to 4, compared to 2.5 ranging from 1 to 6), suggesting a more refractory epileptic phenotype.…”
Section: Comparative Efficacymentioning
confidence: 99%
See 1 more Smart Citation
“…Brivaracetam is a third-generation ASM that is indicated as adjunctive therapy in the treatment of focal seizures (with or without secondary generalisation in the EU) [137,138]. A Cochrane analysis identified six trials evaluating add-on BRV for DREs (Table S1 of the ESM) [139], while BRV has also been analysed in a large number of observational studies in patients with DEEs/DREs [140][141][142][143][144][145][146][147][148]. Brivaracetam is an analogue of LEV that has 15-30 times greater affinity for SV2A and higher brain permeability compared with LEV [149].…”
Section: Brivaracetam (Brv)mentioning
confidence: 99%
“…A study by McGuire et al showed that brivaracetam was safe and efficacious in the reduction of pediatric refractory epilepsy. 54 Perampanel is also another molecule used in the treatment of DS. In a report by Chang et al, perampanel was found to be a safe and effective adjuvant therapy to treat drug resistant epilepsy in young children.…”
Section: New Molecules In Epilepsymentioning
confidence: 99%